(untitled) - McGee, John (New York, 2005)
A hotly-anticipated new textbook brings strategy up-to-date with a fresh and vibrant approach. The author team of Professors John McGee, Howard Thomas and David Wilson combine their extensive experience of teaching and consulting in strategy with cutting edge research to form an exciting new textbook. Marrying comprehensive coverage of strategy with an incisive and analytical approach, the new text is ideal for undergraduate and MBA students taking a strategic management, corporate strategy or business policy module. The book sets out to provide students with an understanding of the core concepts and economics of strategy, laying the foundations for analysing strategy on a variety of levels. With a strong emphasis on practice, the book explores contemporary topics, including risk management, strategic change, corporate governance, the learning organization, and the implementation of strategy for performance and process improvement. The theory is complemented by thorough pedagogy throughout and a range of excellent case examples and longer cases (Case Study Section is included in Text and Cases Version 0077107063) furnish students with the practical applications needed to fully appreciate the consequences of strategic decisions
Keywords: Strategic planning,Decision making